Mycobacterial infection in HIV+ patients detected with a new immunological method (TB test) - Vanacore, R; Paladini, A; Ceretelli, S; Savalli, E; Sbrana, S; Falsini, R; Scasso, A; Ambrogi, F (Allergie et immunologie, 1993)
Antibody response to antigen A60 (a mycobacterial antigen) was evaluated in ELISA in 18 HIV+ subjects with clinical and cultural evidences of mycobacterial infections, in 10 HIV+ subjects without Mycobacterial infections and in 22 healthy donors. We found higher levels of specific IgG in the HIV+ patients with Mycobacterial infections (mean 179.2 +/- 83 U) compared to the values of the donors (mean 92.5 +/- 35.5 U: p < 0.01). This test may be useful in the diagnosis of tuberculosis, but it needs clinical validation.